Abstract gringo - GEBSER, MARTIN; HARRISON, AMELIA; KAMINSKI, ROLAND; LIFSCHITZ, VLADIMIR; SCHAUB, TORSTEN (Theory and practice of logic programming, 2015)
This paper defines the syntax and semantics of the input language of the ASP grounder gringo. The definition covers several constructs that were not discussed in earlier work on the semantics of that language, including intervals, pools, division of integers, aggregates with non-numeric values, and lparse-style aggregate expressions. The definition is abstract in the sense that it disregards some details related to representing programs by strings of ASCII characters. It serves as a specification for gringo from Version 4.5 on.